A low-transmittance lithium tantalate wafer and a preparation method thereof
By using a mixture of silicon-aluminum gel, nickel-based catalyst, and carbon source to generate a reducing gas, reducing the lithium tantalate wafer, the problems of uneven degree of blackening and low efficiency in the traditional blackening process are solved, and efficient and uniform blackening of lithium tantalate wafers are achieved.
Patent Information
- Application Number
- CN202510138629.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The traditional lithium tantalate chip blackening process has problems such as uneven degree of blackening, cumbersome operation, long time for blackening, and low efficiency.
A mixture of silicon-aluminum gel, nickel-based catalyst, and carbon source is used as a reducing agent to generate reducing gases such as carbon monoxide through high-temperature reactions, and the lithium tantalate wafer is reduced to realize the blackening process.
The low light transmittance preparation of lithium tantalate wafers is achieved, the blackening efficiency and yield are improved, and the damage and powderization of the pellets during the pre-reduction process are reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wafer blackening, and in particular to a lithium tantalate wafer with low light transmittance and a preparation method thereof. Background Art
[0002] Wafer blackening technology is an important process for reducing the light transmittance of wafers, especially in multifunctional crystal materials such as lithium niobate and lithium tantalate. These materials are widely used in surface acoustic wave devices, optical communications, optoelectronics and other fields due to their excellent piezoelectric, ferroelectric, pyroelectric and other properties. However, these wafers have high optical transmittance when they are not processed, which will cause strong reflection on the back side after light passes through the substrate during the photolithography process, thereby reducing the resolution and accuracy of the photolithography pattern. In order to solve this problem, wafer blackening technology significantly reduces the light transmittance by changing the optical properties of the wafer, changing its color from colorless and transparent to brown or black. This treatment not only improves the accuracy of the photolithography process, but also reduces the errors that may occur during the photolithography process.
[0003] At present, the main technical route for preparing lithium tantalate black sheets is to embed lithium tantalate wafers in reducing powders (such as carbon powder, iron powder), introduce inert or reducing gas for protection, and heat up to prepare black sheets. The traditional method of using reducing powders to blacken wafers has problems such as uneven "blackening" of the wafers, cumbersome operation, long blackening time, and low efficiency.
[0004] Therefore, it is necessary to develop a new blackening process for lithium tantalate wafers. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the present invention provides a method for preparing a lithium tantalate wafer with low light transmittance. Through a special blackening process, the lithium tantalate wafer is reduced using reducing gases such as carbon monoxide generated by the reaction to obtain a lithium tantalate wafer with low light transmittance.
[0006] Specifically:
[0007] A method for preparing a lithium tantalate wafer with low light transmittance, the steps comprising:
[0008] Step 1: Place the silica-alumina gel, nickel-based catalyst and carbon source in a ball mill, and grind them uniformly for later use;
[0009] Step 2: Place the mixed material in step 1 into a press to make composite carbon balls;
[0010] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0011] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0012] Step 5: evacuate the furnace chamber of the reduction furnace, start the reduction furnace heating system, raise the temperature to 500-550°C, keep warm for 6-8 hours, then cool down. When the temperature reaches 90°C, slowly introduce inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the chip holder, and obtain a lithium tantalate chip with low transmittance.
[0013] Furthermore, in step one, the mass ratio of silica-alumina gel, nickel-based catalyst and carbon source is 2.5-3:1:6-7.
[0014] Furthermore, the nickel-based catalyst is selected from one or more of a nickel-iron bimetallic catalyst, an activated carbon-supported nickel catalyst, and a hydrotalcite-derived nickel-based catalyst.
[0015] Furthermore, the carbon source is selected from one or more of graphite powder, coke powder, and activated carbon powder.
[0016] Furthermore, in step 1, the ball milling rate is 250-300 rpm and the time is 2-3 h.
[0017] Furthermore, deionized water is added as a grinding aid during ball milling in step one.
[0018] Furthermore, after vacuuming in step five, the pressure in the furnace is controlled below 0.01 Pa.
[0019] Furthermore, in step five, the heating rate is 3-5°C / min.
[0020] Furthermore, in step five, the cooling rate is 1-3°C / min.
[0021] In addition, the present invention also provides a lithium tantalate wafer with low light transmittance, which is prepared by the above-mentioned preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial features:
[0023] 1. The present invention adopts a mixture of silica-alumina gel, a nickel-based catalyst, and a carbon source as a reducing agent. The silica-alumina gel will lose the absorbed water and dehydrate itself during the heating process. The generated water vapor reacts with the carbon source under high temperature conditions in the presence of the catalyst to generate reducing gases such as carbon monoxide and hydrogen. These reducing gases can reduce the lithium tantalate wafer to achieve a blackening process, thereby reducing the light transmittance of the lithium tantalate wafer.
[0024] 2. The present invention uses silica-alumina gel as a binder, which can form a viscous solution after adding water. When it is mixed with a nickel-based catalyst and a carbon source, it can effectively wrap the two. In addition, it can also enhance the cohesion of the mixture. This enhanced bonding performance helps to reduce the breakage and pulverization of the pellets during the pre-reduction process, thereby improving the yield rate; in addition, silica-alumina gel can undergo polymerization and gelation reactions during the heating process to form a cross-linked three-dimensional network structure. On the one hand, it can delay the dissipation of water vapor, so that most of the water vapor is locked in the composite carbon sphere, allowing the carbon to react fully with water vapor. On the other hand, this porous structure helps to evenly distribute and transmit the gas, and cooperates with the open pore structure inside the composite carbon sphere to improve the uniformity and thoroughness of the reduction reaction.
[0025] 3. The present invention maintains a vacuum state during the reduction reaction, lowers the reaction temperature of carbon and water vapor, and ensures that sufficient water gas can be generated to provide sufficient reducing gas for the reduction reaction of lithium tantalate wafers. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In order to facilitate those skilled in the art to implement the present invention, some of the reagents used in the embodiments and comparative examples are now described:
[0028] Silica-alumina gel: Qingdao Chenrong New Materials;
[0029] Nickel-based catalyst: activated carbon-supported nickel catalyst, Shanghai Xunkai New Materials Technology Co., Ltd.;
[0030] Carbon source: activated carbon powder, Jining Fangyu Chemical Co., Ltd.
[0031] In order to verify the beneficial effects of the present invention, the following examples and comparative examples are designed to demonstrate the effects.
[0032] Example 1
[0033] A lithium tantalate wafer with low light transmittance, the preparation steps of which include:
[0034] Step 1, the silica-alumina gel, nickel-based catalyst, carbon source in a mass ratio of 2.5:1:6 placed in a ball mill, control the ball milling rate of 250rpm, time 3h, ball milling uniform after standby; add deionized water during ball milling, the mass ratio of deionized water to silica-alumina gel is 1:10;
[0035] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0036] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0037] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0038] Step 5: evacuate the furnace chamber of the reduction furnace, control the gas pressure in the furnace to below 0.01 Pa, start the reduction furnace heating system, increase the temperature to 500°C at a rate of 3°C / min, keep warm for 8 hours, then cool at a rate of 1°C / min, and when the temperature reaches 90°C, slowly introduce argon inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the wafer holder, and obtain a lithium tantalate wafer with low transmittance.
[0039] Example 2
[0040] A lithium tantalate wafer with low light transmittance, the preparation steps of which include:
[0041] Step 1, the silica-alumina gel, nickel-based catalyst, carbon source in a mass ratio of 2.5:1:7 placed in a ball mill, control the ball milling rate of 300rpm, time 2h, ball milling uniform after standby; add deionized water during ball milling, the mass ratio of deionized water to silica-alumina gel is 1:10;
[0042] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0043] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0044] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0045] Step 5: evacuate the furnace of the reduction furnace, control the gas pressure in the furnace to below 0.01 Pa, start the reduction furnace heating system, increase the temperature to 550°C at a rate of 5°C / min, keep warm for 6 hours, then cool at a rate of 3°C / min, and when the temperature reaches 90°C, slowly introduce argon inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the wafer holder, and obtain a lithium tantalate wafer with low transmittance.
[0046] Example 3
[0047] A lithium tantalate wafer with low light transmittance, the preparation steps of which include:
[0048] Step 1, the silica-alumina gel, nickel-based catalyst, carbon source in a mass ratio of 3:1:7 placed in a ball mill, control the ball milling rate of 250rpm, time 2h, ball milling uniform after standby; add deionized water during ball milling, the mass ratio of deionized water to silica-alumina gel is 1:10;
[0049] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0050] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0051] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0052] Step 5: evacuate the furnace chamber of the reduction furnace, control the gas pressure in the furnace to below 0.01 Pa, start the reduction furnace heating system, increase the temperature to 550°C at a rate of 3°C / min, keep warm for 8 hours, then cool at a rate of 3°C / min, and when the temperature reaches 90°C, slowly introduce argon inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the wafer holder, and obtain a lithium tantalate wafer with low transmittance.
[0053] Example 4
[0054] A lithium tantalate wafer with low light transmittance, the preparation steps of which include:
[0055] Step 1, the silica-alumina gel, nickel-based catalyst, carbon source in a mass ratio of 3:1:6 placed in a ball mill, control the ball milling rate of 300rpm, time 3h, ball milling uniform after standby; deionized water was added during ball milling, the mass ratio of deionized water to silica-alumina gel was 1:10;
[0056] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0057] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0058] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0059] Step 5: evacuate the furnace chamber of the reduction furnace, control the gas pressure in the furnace to below 0.01 Pa, start the reduction furnace heating system, increase the temperature to 500°C at a rate of 5°C / min, keep warm for 6 hours, then cool at a rate of 1°C / min, and when the temperature reaches 90°C, slowly introduce argon inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the wafer holder, and obtain a lithium tantalate wafer with low transmittance.
[0060] Example 5
[0061] A lithium tantalate wafer with low light transmittance, the preparation steps of which include:
[0062] Step 1, the silica-alumina gel, nickel-based catalyst, carbon source in a mass ratio of 2.5:1:7 placed in a ball mill, control the ball milling rate of 250rpm, time 3h, ball milling uniform after standby; add deionized water during ball milling, the mass ratio of deionized water to silica-alumina gel is 1:10;
[0063] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0064] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0065] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0066] Step 5: evacuate the furnace chamber of the reduction furnace, control the gas pressure in the furnace to below 0.01 Pa, start the reduction furnace heating system, increase the temperature to 550°C at a rate of 4°C / min, keep warm for 7 hours, then cool at a rate of 2°C / min, and when the temperature reaches 90°C, slowly introduce argon inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the wafer holder, and obtain a lithium tantalate wafer with low transmittance.
[0067] Comparative Example 1
[0068] A lithium tantalate wafer, the preparation steps of which include:
[0069] Step 1, the nickel-based catalyst, the carbon source in a mass ratio of 2.5:1:6 placed in a ball mill, control the ball milling rate of 250rpm, time 3h, ball milling uniform after standby; deionized water was added during ball milling, the mass ratio of deionized water to carbon source was 1:20;
[0070] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0071] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0072] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0073] Step 5, evacuate the furnace of the reduction furnace, control the gas pressure in the furnace to below 0.01Pa, start the reduction furnace heating system, increase the temperature to 500°C at a rate of 3°C / min, keep warm for 8 hours, then cool at a rate of 1°C / min, and when the temperature reaches 90°C, slowly introduce argon inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the wafer holder, and obtain the lithium tantalate wafer.
[0074] Comparative Example 2
[0075] A lithium tantalate wafer, the preparation steps of which include:
[0076] Step 1, the silica-alumina gel, nickel-based catalyst, carbon source in a mass ratio of 2.5:1:6 placed in a ball mill, control the ball milling rate of 250rpm, time 3h, ball milling uniform after standby; add deionized water during ball milling, the mass ratio of deionized water to silica-alumina gel is 1:10;
[0077] Step 2: Transfer the mixed material of step 1 into a spherical mold, place it on a press, apply a pressure of 5 MPa on the press, and maintain the pressure for 10 minutes to make a composite carbon ball;
[0078] Step 3, cleaning the surface of the lithium tantalate wafer to be processed;
[0079] Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace;
[0080] Step 5: introduce argon inert gas into the reduction furnace, start the reduction furnace heating system, increase the temperature to 500°C at a rate of 3°C / min, keep warm for 8 hours, then cool to room temperature at a rate of 1°C / min, take out the wafer holder, and obtain the lithium tantalate wafer.
[0081] The transmittance of the lithium tantalate wafers prepared in Examples 1-5 and Comparative Examples 1-2 was tested under exposure light sources with a wavelength of 350nm to 450nm, and the lithium tantalate wafers that were not blackened were used as a blank group. The test results are shown in the following table:
[0082]
[0083] By comparing with the blank group, it can be found that the transmittance of Examples 1-5 is close to 0%, indicating that the reduction effect is good.
[0084] Compared with Examples 1-5, the reducing component of Comparative Example 1 lacks the silica-alumina gel. Although the transmittance is reduced, the effect is not as good as that of Examples 1-5.
[0085] Compared with Examples 1-5, in Comparative Example 2, no vacuum was performed during the reduction process, and the transmittance was similar to that of the blank group, indicating that the reduction reaction did not proceed.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lithium tantalate wafer with low light transmittance, characterized in that: The steps include: Step 1: Place the silica-alumina gel, nickel-based catalyst and carbon source in a ball mill, and grind them uniformly for later use; Step 2: Place the mixed material in step 1 into a press to make composite carbon balls; Step 3, cleaning the surface of the lithium tantalate wafer to be processed; Step 4: Load the lithium tantalate wafer cleaned in step 3 into the wafer holder and place it in the reduction furnace, and evenly spread the composite carbon balls obtained in step 2 in the reducing agent charging box and place it at the bottom of the reduction furnace; Step 5: evacuate the furnace chamber of the reduction furnace, start the reduction furnace heating system, raise the temperature to 500-550°C, keep warm for 6-8 hours, then cool down. When the temperature reaches 90°C, slowly introduce inert gas to restore the pressure in the furnace to normal pressure, continue to cool to room temperature, take out the chip holder, and obtain a lithium tantalate chip with low transmittance.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of silica-alumina gel, nickel-based catalyst and carbon source is 2.5-3:1:6-7.
3. The preparation method according to claim 1, characterized in that: The nickel-based catalyst is selected from one or more of a nickel-iron bimetallic catalyst, an activated carbon-supported nickel catalyst, and a hydrotalcite-derived nickel-based catalyst.
4. The preparation method according to claim 1, characterized in that: The carbon source is selected from one or more of graphite powder, coke powder and activated carbon powder.
5. The preparation method according to claim 1, characterized in that: In step 1, the ball milling rate is 250-300 rpm and the time is 2-3 h.
6. The preparation method according to claim 1, characterized in that: In step 1, deionized water is added during ball milling as a grinding aid.
7. The preparation method according to claim 1, characterized in that: After vacuuming in step 5, the pressure in the furnace is controlled below 0.01 Pa.
8. The preparation method according to claim 1, characterized in that: In step 5, the heating rate is 3-5°C / min.
9. The preparation method according to claim 1, characterized in that: In step 5, the cooling rate is 1-3°C / min.
Citation Information
Patent Citations
Lithium tantalate wafer and blackening method therefor
CN112714805A